PROTOKOL SCOPING REVIEW: ANTI STIGMA-BASED PSYCHOEDUCATION ON CAREGIVERS OF PATIENTS WITH SCHIZOPHRENIA AND COMMUNITY - Indriati Indriati; Agus Suwandono; Budi Anna Keliat; Anies (Jurnal Ilmu Keperawatan Jiwa, 2023)
ABSTRACT Caregivers and community stigmatize People With Schizophrenia (PWS). This phenomenon causes a very detrimental impact, including low reintegration of PWS into society and worsening of their social function. Anti-stigma-based psychoeducation is needed to de-stigmatize caregivers of PWS and community, but previous research has not clearly identified this. This scoping review protocol will guide the authors to map previous research related to anti-stigma based psychoeducation on caregivers of PWS and community. Scoping review uses the Arksey & O'Malley approach. Literature search keywords are based on Population, Content, and Context (PCC). The flow of literature screening followed the PRISMA ScR flowchart. The types of literature used were clinical trial, meta analysis, randomized controlled trial, review, and systematic review, in English from PubMed, CINAHL (Ebsco), and ScienceDirect databases. Year of publication: Last 10 years (January 2013 - January 2023). In the final stage, the authors conducted an analysis, namely basic numerical analysis and then continued with thematic analysis. Keywords: schizophrenia, psychoeducation, anti-stigma, caregivers, and community